2014
DOI: 10.1097/mib.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Measurement of Endoscopic Disease Activity and Mucosal Healing in Crohnʼs Disease

Abstract: Both the endoscopic evaluative instrument selected and the definition chosen for mucosal healing affect the validity of assessing endoscopic disease activity during a clinical trial for CD. Currently, the CDEIS and SES-CD have the most data regarding operating properties; however, further validation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 93 publications
(75 reference statements)
1
44
0
Order By: Relevance
“…[1][2][3] The objective of medical treatment has also evolved, from the induction of clinical remission to the healing of mucosal lesions. 4 However, irritable bowel syndrome (IBS) can occur even in the absence of organic abnormalities, and can be associated with gastrointestinal symptoms such as diarrhea and constipation. [5][6][7] Conventionally, IBS and IBD have been considered completely separate diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The objective of medical treatment has also evolved, from the induction of clinical remission to the healing of mucosal lesions. 4 However, irritable bowel syndrome (IBS) can occur even in the absence of organic abnormalities, and can be associated with gastrointestinal symptoms such as diarrhea and constipation. [5][6][7] Conventionally, IBS and IBD have been considered completely separate diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Both CDEIS and SES-CD are validated scoring systems for CD. Surprisingly, we found that only one-fifth use the CDEIS, and 9.6% the SES-CD, while the CDEIS is known as time consuming and complex [19,20,48].…”
Section: Discussionmentioning
confidence: 88%
“…There are a number of endoscopic disease activity scores that assist endoscopists, but few have been properly evaluated and validated in large cohorts. Good examples are the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) for ulcerative colitis (UC) [16,17], the Crohn's Disease Endoscopic Index of Severity (CDEIS) and the Simple Endoscopic Score (SES-CD) for Crohn's disease (CD) [18][19][20]. Practical and commonly used definitions for MH such as "the complete resolution of the visible alteration or lesions" [21], or endoscopic Mayo score ≤ 1 [22] have the disadvantage of higher interobserver variability and limited accuracy [9,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…11 Although symptom-based metrics such as resolution of pain, bleeding, and diarrhea hypothetically might be adequate surrogates for MH, a strong correlation has not been demonstrated between these methods of assessment. 5,6,12,13 A key feature of IBD is the repetitive nature in which epithelial damage occurs, often before clinical signs manifest. 14,15 Thus, the chronicity of damage often is well-established at the time of presentation, and healing often lags behind symptomatic improvement.…”
Section: Mh: Clinical Relevance and Current Definitionsmentioning
confidence: 99%